The Imports of Processed Fruit Products From Ukraine to the EU Member States After Trade Liberalization in 2022 - KIERCZYŃSKA SYLWIA (Zagadnienia Ekonomiki Rolnej)
The aim of the study was to analyze how the decision to establish free trade between Ukraine and the European Union after the Russian invasion of Ukraine influenced the volume of imports of selected fruit products to the EU Member States, especially to Poland.